Prime-boost vectored malaria vaccines: progress and prospects. - Hill, A; Reyes-Sandoval, A; O'Hara, G; Ewer, K; Lawrie, A; Goodman, A; Nicosia, A; Folgori, A; Colloca, S; Cortese, R; Gilbert, S; Draper, S (2010)
The difficulty of inducing protective immunity through antibodies against sporozoites led to efforts to assess vectored vaccines as a means of inducing protective T-cell immunity against the malaria liver-stage parasite. Although DNA vectored vaccines used alone were poorly immunogenic and not protective, high levels of parasite clearance in the liver has been achieved with viral vectored vaccines used in heterologous prime-boost regimes. Such vectored vaccination regimes represent one of only two approaches that have induced repeatable partial efficacy in human P. falciparum subunit vaccine trials. Interestingly, vectors expressing the TRAP antigen have been consistently been more immunogenic and protective than vectors expressing the circumsporozoite protein in human trials. However, sterile protection requires induction of very potent T-cell responses that are currently only achievable with heterologous prime-boost regimes. Recently, simian adenoviruses have been assessed as priming agents in Adenovirus-MVA regimes in both phase I and phase IIa trials in the UK, based on very promising pre-clinical results showing better immunogenicity and efficacy than previous prime-boost regimes. The same vectors are also being assessed clinically expressing blood-stage antigens, attempting to induce both protective antibodies and T cells as recently demonstrated in murine efficacy studies. These viral vectors now provide a major option for inclusion in a high efficacy multi-stage malaria vaccine that should achieve deployable levels of efficacy in endemic settings.